Criteria and Provisions for Efficient Implementation of Macro-Projects of International Sport Event Tourism - TEMNYK, Inha O. (Journal of Environmental Management and Tourism; Vol 8 No 6 (2017): JEMT Volum VIII Issue 6(22) Fall 2017DO - 10.14505//jemt.v8.6(22).18, 2018)
In this paper, the problems of effective implementation of large-scale projects of international sporting event tourism are considered. It has been shown that large-scale sports events in the system of event tourism play a significant role and have a steady dynamic of development, that is why they form a circle of scientific interests both in the sphere of international tourism marketing and in the field of project management. The features of sport large-scale events and their management are analyzed, which, as it is defined, requires the use of a complex of measures and instruments within the limits of macro-projects of international sports tourism. The concept of macro-projects of international sport tourism is defined, the necessity of application of criteria of effective realization of data of macro projects in accordance with the system of requirements for their effectiveness is revealed and substantiated. Particular attention is paid to the necessity of searching for scientifically grounded ways of providing organizers of large-scale projects of sport event tourism with the fullest implementation of project tasks in the process of organizing sport events, as well as on the formation of a scientific basis for the selection of projects of sports event tourism of a certain group of large-scale projects (macro projects), management of which, based on their specificity, significance, scale and number of structures involved in the organization, has certain features. On the basis of the conducted study of the results of holding a large event in Ukraine, the Euro-2012, a comparative analysis of this event and sports events that were implemented in other countries, the author identified a list of factors that influence the effective implementation of similar to the Euro-2012 events, problems of realization and ways of overcoming them.